Rapid Complete Acetabular Destruction in Metal-on-Metal Total Hip Arthroplasty - Pean, Christian A. (J Am Acad Orthop Surg Glob Res Rev, 2018)
Adverse local tissue reaction, osteolysis, and subsequent increased incidence of failure have been associated with metal-on-metal (MoM) total hip arthroplasty (THA). We present the case of a 68-year-old woman with rheumatoid arthritis who has undergone left THA with a MoM bearing. Seven years postoperatively, she presented with 6 weeks of severe left hip pain. Sequential radiographs and advanced imaging demonstrated a rapid onset of extensive acetabular osteolysis with pelvic discontinuity and pseudotumor formation. She underwent revision THA using a cup-cage construct with a satisfactory outcome. In this article, we review current evidence-based management options for pelvic discontinuity, as well as other complications related to MoM THA.